English Borrowings in Contemporary Italian: a Linguistic-Cognitive Aspect - Kondruk, Veronica (Studia Philologica, 2024)
In the article, the linguistic-cognitive aspect of English borrowings in contemporary Italian is considered. The globalization of the English language is one of the driving forces that raises questions about language contacts and interactions in modern linguistics. The presented scientific investigation aims to identify the linguistic-cognitive features of the usage of English borrowings in Italian-language news discourse. The linguistic-cognitive approach allows for analyzing the behavior of speakers and the organization of conceptual space in human consciousness. The article discusses the factors and phenomena to which users of the linguistic code are subordinate, as well as the impulses of internal and external systems that accelerate the penetration of English equivalents into the Italian language. English borrowings are revealed taking into account the universal characteristics of open systems. The article asserts that the analyzed linguistic-cognitive processes are universal-systemic, as they can be applied to the analysis of factors and phenomena of various natures, including linguistic and psychological.